Keefektifan Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Peserta Didik Pada Materi Stoikiometri Di SMA Swasta Tarbiyah Labuhanhaji Aceh Selatan - Lindawati, Musyrifah (Yana Research, 2023)
The learning model used by teachers should be able to help students' analysis process. However, student learning outcomes in the field of Chemistry are still worrying, this can be seen from the results of the final school exams. One learning model that can improve student learning outcomes is the problem based learning (PBL) learning model. The formulation of the problem in this research is whether there is a difference in the learning outcomes of students who are taught with the problem based learning model and without the problem based learning model on Stoichiometry material at Tarbiyah Labuhanhaji Private High School? The research method used is quasi-experimental research using one experimental class and one control class. Sampling was carried out using cluster sampling. In this study the sample consisted of two classes, namely class X-1 as the experimental class and class X-2 as the control class. Data collection was carried out using tests. Based on the research results, the results of the independent sample t-test analysis were obtained with a significance level of 0.000 <0.05, which means that H0 was rejected and Ha was accepted, thus indicating that the learning outcomes of students who were taught using the problem based learning model were higher than the learning outcomes of students. which is taught without a problem based learning model on Stoichiometry material at Tarbiyah Labuhanhaji Private High School.